2020
DOI: 10.1371/journal.pone.0233616
|View full text |Cite
|
Sign up to set email alerts
|

Comparing transcriptome expression profiles to reveal the mechanisms of salt tolerance and exogenous glycine betaine mitigation in maize seedlings

Abstract: Salt stress is a common abiotic stress that limits the growth, development and yield of maize (Zea mays L.). To better understand the response of maize to salt stress and the mechanism by which exogenous glycine betaine (GB) alleviates the damaging effects of salt stress, the morphology, physiological and biochemical indexes, and root transcriptome expression profiles of seedlings of salt-sensitive inbred line P138 and salt-tolerant inbred line 8723 were compared under salt stress and GB-alleviated salt stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…The reaction volume included 10 μL SuperReal PreMix Plus, 6 μL ddH 2 O, 0.8 μL forward primer (10 μmol/L), 0.8 μL reverse primer, 0.4 μL Rox reference dye and 2 μL template cDNA. The amplification procedure was described with reference to Chen et al (2020) . Actin gene was used as the internal reference gene ( Zeng et al, 2019 ), and the gene expression was analyzed by 2 –ΔΔCT calculation method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction volume included 10 μL SuperReal PreMix Plus, 6 μL ddH 2 O, 0.8 μL forward primer (10 μmol/L), 0.8 μL reverse primer, 0.4 μL Rox reference dye and 2 μL template cDNA. The amplification procedure was described with reference to Chen et al (2020) . Actin gene was used as the internal reference gene ( Zeng et al, 2019 ), and the gene expression was analyzed by 2 –ΔΔCT calculation method.…”
Section: Methodsmentioning
confidence: 99%
“…Maize ( Zea Mays L.) is the most widely grown and important food, feed, and industrial feedstock crop in the world ( Niu et al, 2019a ). A disadvantage of maize is that it is sensitive to a variety of abiotic stresses (such as salt stress, drought stress, and low temperature stress) during its seedling life ( Chen et al, 2020 ). In China, maize planting areas are mostly distributed in arid and semi-arid areas, accounting for 2/3 of cultivated land ( Du et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments also proved the benefit of the external application of betaine on the plant under salt stress. Experiments by Chen et al showed that exogenous glycine betaine mitigated salt stress in maize seedlings [57]. In addition, betaine is involved in many metabolic processes.…”
Section: Organic Substancesmentioning
confidence: 99%
“…Comparing the difference in transcriptional levels between tolerant and sensitive genotypes under stress conditions, the genes related to stress tolerance can be isolated. A transcriptomics study also revealed different upand downregulated transcriptional factors such as MYB, MYBrelated, AP2-EREBP, NAC, and WRKY (Chen F. et al, 2020). This transcriptional profiling study gives a better insight into the understanding of the key components in the plant salt tolerance network which is important for developing more salt-tolerant plants.…”
Section: Transcriptomicsmentioning
confidence: 77%